UNIVERSALITAS EKARISTI Tinjauan Teologis Atas Ciri Kosmik, Sosial dan Kulturalnya - E.P.D. Martasudjita (P3TK, Sanata Dharma University, 2014)
Question on universality of the Eucharist stems from plurality of its celebration and understanding in various ecclesial communities. The question itself pertains to Eucharistic ecclesiology. How a Eucharistic celebration has built an ecclesial unity throughout its history, all over the world? This article aims to contribute to this respective discussion especially from the perspective of the teachings of Vatican II as well as the thoughts of St. John Paul II and Pope emeritus Benedict XVI. The discussion on the cosmic character as well as eschatological, social and cultural of the Eucharist demonstrates that the plurality of its celebration and understanding in various ecclesial communities are not necessarily confusing its universal meaning, but enriching it. This should happen especially when a Eucharistic celebration remain faithfully in expressing the mystery of Christ and therefore the nature of the Church.